1987
DOI: 10.1172/jci113222
|View full text |Cite
|
Sign up to set email alerts
|

Human placental transport of cimetidine.

Abstract: This study addresses the mechanism of transport of the H2-receptor antagonist, cimetidine, by the human placenta. A 4-h recycling perfusion of a single placental cotyledon of normal, term, human placenta was used. At a maternal concentration of 1 ug/ml, cimetidine clearance from the maternal circulation was 0.58±0.16 ml/min per g placenta, a rate about one third that of antipyrine. There was no evidence of cimetidine metabolism by the placenta. Transfer of cimetidine from maternal to fetal compartments showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Here, K is the slope of drug appearance in the recipient reservoir, V is the recipient perfusate volume, and C is the mean drug concentration in the donor circuit. This equation is appropriate for compounds that do not reach equilibrium in the model (Schenker et al, 1987). All graphical and statistical analyses were performed using GraphPad Prism 3.0.…”
Section: Methodsmentioning
confidence: 99%
“…Here, K is the slope of drug appearance in the recipient reservoir, V is the recipient perfusate volume, and C is the mean drug concentration in the donor circuit. This equation is appropriate for compounds that do not reach equilibrium in the model (Schenker et al, 1987). All graphical and statistical analyses were performed using GraphPad Prism 3.0.…”
Section: Methodsmentioning
confidence: 99%
“…In several experiments antipyrine and 3H-~-glucose were used as reference molecules. Antipyrine, a readily diffusable lipophillic substance, is added to the maternal perfusate at a concentration of 12 mg/100 mL, a level at which no antipyrine metabolites are detected (43). Antipyrine concentrations in maternal and fetal perfusates are used to calculate clearance and an exchange index, which references the exchange of any compound in question to the clearance of antipyrine, for taurine.…”
Section: Placental Perfusionmentioning
confidence: 99%
“…In the present study, cimetidine was used to comprehensively describe the role of Bcrp in maternal-to-fetal and fetalto-maternal transport. Cimetidine was chosen as a model substrate for its convenient properties; it is a BCRP substrate that is not recognized by human P-gp , it weakly binds to plasma proteins, and its biotransformation by placental enzymes is negligible (Schenker et al, 1987). In addition, cimetidine passive diffusion through biological membranes is delayed by its physical-chemical properties as shown in transepithelial passage or placental transport (Ching et al, 1987;Schenker et al, 1987); this seems to be an important feature to study substrate interactions with an efflux transporter (Eytan et al, 1996;Lentz et al, 2000).…”
mentioning
confidence: 99%
“…In a follow-up study, the authors suggested that an active transporter from the fetal to the maternal circulation might be responsible for this discrepancy (Ching et al, 1985). In contrast, when investigated in the dually perfused human placenta, two papers concluded that transport of cimetidine was very slow and occurred by passive diffusion with lack of saturation kinetics (Ching et al, 1987;Schenker et al, 1987). These contrasting findings might be explained by interspecies differences; however, one has to realize that these studies were performed before efflux transporters were discovered and described, with limited range of cimetidine concentrations, and without the option to use appropriate inhibitors.…”
mentioning
confidence: 99%